ChemInform Abstract: Fe‐Promoted Chlorobenzylation of Terminal Alkynes Through Benzylic C(sp3)—H Bond Functionalization. Issue 31 (14th July 2016) - Shi, Jiang‐Ling; Zhang, Ji‐Cheng; Wang, Bi‐Qin; Hu, Ping; Zhao, Ke‐Qing; Shi, Zhang‐Jie
Abstract: The title process provides alkenyl chlorides with complete regio‐ and high E‐selectivity.